Analisis Hubungan Waktu Tunggu terhadap Kepuasan Pasien di Puskesmas: Literature Review - Shanti Pawitra Paramesthi; Diansanto Prayoga (Universitas Airlangga, 2023)
Background: The community as recipients of health services certainly wants quality health services. To know the quality or not of a health service can be seen from the waiting time and patient satisfaction which is an indicator of the success of health services. Waiting time has an important role in giving a good first impression to the patient. Objectives: This study aims to determine the relationship between waiting time and patient satisfaction at the puskesmas. Methods: The study uses a literature review method based on theis based on the PRISMA protocol. The literature reviewed is literature that discusses patient satisfaction based on waiting time for services at the puskesmas. Results: The search results for articles in the Google Scholar and ResearchGate databases show that there are 4 (four) journals that meet the criteria. These four articles have been filtered using keywords, inclusion and exclusion criteria, published between 2018-2021. All articles reviewed are Indonesian language articles with quantitative research types. Conclusions: Based on the 4 (four) journals that have been reviewed, 3 (three) of them show that the length of waiting time for services is related to patient satisfaction at the puskesmas.